Exploring the individual experiences of women facing cervical cancer: a study on sexual life changes, emotional responses, and physical adaptations - Kurniasih, Dwi; Goretik, Maria; Siskawati, Siskawati (Journal of Maternal and Child Health, 2024)
Background: Cervical cancer is one of the significant cancers in the female reproductive organs, namely the cervix. Diagnosis and treatment of cervical cancer not only affect physical health, but also psychologically and socially, especially in the context of sexual life. Physical and emotional changes that arise from treatments such as chemotherapy and radiotherapy can significantly affect women's sexual function, cause anxiety, and change the dynamics of interpersonal relationships. Subjects and Method: This study uses a qualitative approach with a descriptive phenomenological design. Data collection was conducted through in-depth interviews with five cervical cancer patients undergoing treatment at the Dr. Soedarso General Hospital, Pontianak. Data were analyzed using a thematic analysis approach to identify key themes in the experiences of changes in sexual life, emotional responses, and physical adaptation of the participants. Results: The results of the study showed that cervical cancer patients experienced various changes in their sexual lives after undergoing treatment. The main challenges faced were physical discomfort that leads to difficulty in achieving sexual satisfaction, diversion of sexual activities to meet the needs of partners, and complex emotional responses such as anxiety, depression, and feelings of hopelessness. Physically, adaptation to changes such as persistent fatigue and digestive changes were also significant problems. Conclusion: This study highlights the importance of comprehensive psychosocial support in caring for women with cervical cancer, including a holistic approach that considers physical, emotional, and interpersonal aspects. The findings also highlight the need for better sexual health education for patients and their partners, as well as the important role of families in providing adequate support. By better understanding the experiences of women with cervical cancer, it is hoped that their care and overall quality of life can be improved.